Bimbingan Kelompok Karyawista Bagi Peningkatan Spiritual Well-Being - Maesaroh, Maesaroh; Sugiyadi; Hijrah Eko Putro (Technocouns: Journal of Technology in Guidance and Counseling, 2024)
This research aims to determine field trip group guidance services for improving spiritual well-being among PC IMM Magelang Raya members. The type of research used in this research is Pre-Experimental Design with One Group Pretest Posttest Design type. The data collection method was carried out using a spiritual well-being scale which had been tested for validity and reliability with the help of SPSS 26 for Windows. The research results show that field trip group guidance is effective in improving the spiritual well-being of PC IMM Magelang Raya members. It was proven by the results of the pretest and posttest that the highest change score after being given treatment was 36.6 or the equivalent of 34%. The comparison of pretest and posttest scores above is confirmed by changes in the behavior of PC IMM Magelang Raya members, namely, individual changes that were visible before being given counseling services and after being given field trip group guidance.